Examination of sex-related differences in intestinal and gonadal lipid metabolism in the sea cucumber Apostichopus japonicus - Zhang, Shuangyan; Ru, Xiaoshang; Zhang, Libin; Gonçalves, David; Yang, Hongsheng (Aquaculture, 2023)
Reproduction of the sea cucumber Apostichopus japonicus is critical for aquaculture production. Gonadal development is the basis of reproduction, and lipids, which are among the main nutrients required for gonadal development, directly affect reproduction. We investigated whether gonadal and intestinal lipid metabolism differed between male and female A. japonicus. Transcriptome analysis of the intestines of sexually mature male and female wild-caught individuals revealed differences in gene expression, with 27 and 39 genes being up-regulated in females and males, respectively. In particular, the expression of the fatty acid synthase gene was higher in males than in females. Metabolome analysis of the gonads identified 141 metabolites that were up-regulated and 175 metabolites that were down-regulated in the testes compared with the ovaries in the positive/negative mode of an LC-MS/MS analysis. A variety of polyunsaturated fatty acids were found at higher concentrations in the testes than in the ovaries. 16 s rDNA sequencing analysis showed that the composition and structure of the intestinal microbiota were similar between males and females. These results suggest that sex differences in intestinal metabolism of A. japonicus are not due to differences in the microbiota, and we speculate that gonadal metabolism may be related to intestinal morphology. This information might be useful in improving the reproductive efficiency of sea cucumbers in captivity.
Keywords: Gonads; Intestines; Lipid metabolism; Sea cucumber; Sex differences

Effects of a High-Fat Diet on Intestinal and Gonadal Metabolism in Female and Male Sea Cucumber Apostichopus japonicus - Zhang, Shuangyan; Ru, Xiaoshang; Zhang, Libin; Gonçalves, David; Yang, Hongsheng; Xu, Jialei (Biology, 2023)
Parental nutrient reserves are directly related to reproductive performance in sea cucumbers. This study focused on the lipid requirements of male and female sea cucumbers Apostichopus japonicus during the reproductive stage and analyzed their physiological responses to a high-fat diet (HFD). The intestinal lipid metabolites and microbiome profile changed significantly in animals fed with the HFD, as given by an upregulation of metabolites related to lipid metabolism and an increase in the predominance of Proteobacteria in the microbiome, respectively. The metabolic responses of male and female sea cucumbers to the HFD differed, which in turn could have triggered sex-related differences in the intestinal microbiome. These results suggest that the lipid content in diets can be differentially adjusted for male and female sea cucumbers to improve nutrition and promote reproduction. This data contributes to a better understanding of the reproductive biology and sex differences of sea cucumbers.
Number: 2
Keywords: high-fat diet; intestinal microbes; physiological metabolic responses; sea cucumber; sex differences